2022
DOI: 10.1007/s12520-022-01613-3
|View full text |Cite
|
Sign up to set email alerts
|

Isotopic insights into the early Medieval (600–1100 CE) diet in the Luistari cemetery at Eura, Finland

Abstract: In this article, we present the results of an isotopic study of diet for the early medieval (Merovingian, Viking, Early Christian) humans buried in the unique Luistari cemetery at Eura (ca. 600–1400 CE), southwestern Finland, the largest cemetery of the region. Isotope analysis was conducted on 37 humans for dentine and bone collagen (δ13C, δ15N, and δ34S), and five of them were also studied using compound-specific nitrogen isotope analysis. Dental enamel and/or bone carbonate δ13C values were studied from alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 118 publications
0
1
0
Order By: Relevance
“…The utilization of both 𝛿 13 C coll and 𝛿 13 C carb in isotopic studies, therefore, provides a more holistic estimate of several dietary inputs. In Europe, some studies have made use of both components (Dotsika et al, 2022 ; Etu‐Sihvola et al, 2022 ; Grupe et al, 2009 ; Gugora et al, 2022 ; Olsen et al, 2016 ; Reitsema et al, 2010 ; Toyne et al, 2022 ; Yoder, 2012 ; Zechini et al, 2021 ). Although 𝛿 13 C coll data from these studies suggested that dietary protein was primarily derived from C 3 resources, the differences in the 𝛿 13 C carb values among the individuals at certain sites indicated that some individuals may have consumed more C 4 or marine foods than others (Dotsika et al, 2022 ; Reitsema et al, 2010 ; Yoder, 2012 ), demonstrating the utility of analyzing 𝛿 13 C carb alongside 𝛿 13 C coll values.…”
Section: Introductionmentioning
confidence: 99%
“…The utilization of both 𝛿 13 C coll and 𝛿 13 C carb in isotopic studies, therefore, provides a more holistic estimate of several dietary inputs. In Europe, some studies have made use of both components (Dotsika et al, 2022 ; Etu‐Sihvola et al, 2022 ; Grupe et al, 2009 ; Gugora et al, 2022 ; Olsen et al, 2016 ; Reitsema et al, 2010 ; Toyne et al, 2022 ; Yoder, 2012 ; Zechini et al, 2021 ). Although 𝛿 13 C coll data from these studies suggested that dietary protein was primarily derived from C 3 resources, the differences in the 𝛿 13 C carb values among the individuals at certain sites indicated that some individuals may have consumed more C 4 or marine foods than others (Dotsika et al, 2022 ; Reitsema et al, 2010 ; Yoder, 2012 ), demonstrating the utility of analyzing 𝛿 13 C carb alongside 𝛿 13 C coll values.…”
Section: Introductionmentioning
confidence: 99%